A Comprehensive Review of Hepatitis A, B, and C Vaccine Comparisons - Yahya Ayasy AlMuhandis; Nadila Suci Nugraha; Rosis Ainin Faqihah (Yayasan Cendekia Gagayunan Indonesia, 2025)
Hepatitis is a disease that causes inflammation of the liver due to viral infection or non-infectious factors, such as drug use and metabolic disorders. This disease is divided into hepatitis A, B, and C with hepatitis B and C potentially developing into cirrhosis and liver cancer. This study aims to compare hepatitis A, B, and C vaccines based on virus characteristics, production methods, target recipients, administration methods, mechanisms of action, and effectiveness. The method used is a literature review from scientific databases such as PubMed and Google Scholar. The results show that hepatitis A and B vaccines are widely available with an effectiveness of more than 90%, while hepatitis C does not yet have a vaccine, so its treatment relies on Direct-Acting Antivirals (DAAs) therapy with a success rate of more than 95%. Although the hepatitis B vaccine is effective, challenges remain in global vaccination coverage, especially in developing countries. Public awareness and access to more affordable therapy are important factors in efforts to prevent and control hepatitis.